A clay‐based formulation of the herbicide imazaquin containing exclusively the biologically active enantiomer. Issue 7 (28th January 2019) - López‐Cabeza, Rocío; Poiger, Thomas; Cornejo, Juan; Celis, Rafael
Abstract: BACKGROUND: Imazaquin is a chiral herbicide which displays high mobility in soils. Like other imidazolinones, imazaquin is available for use only as racemic mixture of its enantiomers. In this work, several clay materials were assayed as adsorbents of imazaquin, and then the most suitable material was selected to prepare a clay‐based slow release imazaquin nanoformulation containing exclusively the biologically active R ‐enantiomer. Next, laboratory experiments were conducted to illustrate the benefits of using the clay‐based R ‐imazaquin formulation over the free (non‐supported) racemic herbicide or the free pure R ‐imazaquin enantiomer regarding its leaching behavior and bioefficacy. RESULTS: The clay material selected as a carrier for R ‐imazaquin, hexadecyltrimethylammonium‐saturated montmorillonite (SA‐HDTMA), combined a high affinity for the herbicide and a high stability of the clay‐herbicide adsorption complex. In a simulated scenario of high water input shortly after herbicide application, the clay‐based R ‐imazaquin formulation displayed reduced leaching and increased bioefficacy compared to free racemic imazaquin and free R ‐imazaquin. CONCLUSION: The new clay‐ R ‐imazaquin formulation prepared, besides avoiding the environmental impact caused by the application of the less active S ‐enantiomer, reduced the herbicide leaching losses and prolonged the herbicidal activity, by increasing the residence time of the herbicide in the topsoil. © 2018 Society of Chemical Industry Abstract : The use of a clay‐ R ‐imazaquin formulation avoided the application of the less active S ‐imazaquin enantiomer, reduced herbicide leaching losses, and maintained the active enantiomer in the topsoil.